2022
DOI: 10.1038/s41598-022-05812-9
|View full text |Cite
|
Sign up to set email alerts
|

Automatic real-time occupational posture evaluation and select corresponding ergonomic assessments

Abstract: The objective is to develop a system to automatically select the corresponding assessment scales and calculate the score of the risk based on the joint angle information obtained from the imaged process (OpenPose) via image-based motion capture technology. Current occupational assessments, for example, REBA, RULA, and OWAS were used to evaluate the risk of musculoskeletal disorders. However, the assessment result would not be reported immediately. Introducing real-time occupational assessments in different wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 31 publications
1
6
1
Order By: Relevance
“…The CV system was robust to dynamic light conditions and the mean RMSE of all joint angles across different tasks is in line with earlier studies (Kim et al, 2021;Lin et al, 2022). Figure 3 shows that in comparison with other joint angles, the head flexion/extension angle had higher variance across tasks.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The CV system was robust to dynamic light conditions and the mean RMSE of all joint angles across different tasks is in line with earlier studies (Kim et al, 2021;Lin et al, 2022). Figure 3 shows that in comparison with other joint angles, the head flexion/extension angle had higher variance across tasks.…”
Section: Discussionsupporting
confidence: 86%
“…Based on the findings discussed above, this study was unable to confirm the applicability of the proposed CV system directly for RAMP ergonomic assessment in industry, even though previous studies from lab environments suggested otherwise (Kim et al, 2021;Lin et al, 2022;Massiris Fernández et al, 2020).…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Image processing algorithms are often combined with the application of neural networks [17,19,20], which results in high classification accuracy for both person-specific and general classification tasks. Specifically, the system presented in Ref [18] has a reported recognition rate of high-risk work postures comparable to the baseline assessment of an ergonomic expert. Overall, image-processing-based approaches provide a non-disruptive and accurate approach for classifying work postures, which do not require wearable sensors or devices and are most commonly employed for manufacturing or handling tasks.…”
Section: Introductionmentioning
confidence: 97%
“…These solutions employ camera and imaging setups that record workers and access their work posture and the connected health risks. This approach can be used for computer-related office work [17] and physically demanding high-risk work, such as maintenance, handling and assembly [18]. Image processing algorithms are often combined with the application of neural networks [17,19,20], which results in high classification accuracy for both person-specific and general classification tasks.…”
Section: Introductionmentioning
confidence: 99%